"Measure my teeth and you'll know what I ate": The molar ratio method and an updated interpretation of the diet of Nyctereutes sinensis (Carnivora, Canidae). (14th March 2019) - Bartolini Lucenti, Saverio
Abstract: The molar ratio method presented by Acta Zoologica ( 98, 2016, 292) is a valid way to estimate the dietary differences between extant subspecies of the raccoon dog genus, Nyctereutes . Particularly, higher values of the molar ratio implies more omnivous diet than lower ones. With the same technique is possible to infer variations in the diet of extinct species. For the two Plio‐Pleistocene fossil species Nyctereutes sinensis and Nyctereutes megamastoides, the authors estimate a more carnivorous diet for the latter in comparison to the former that has much higher values. This fact contrast with the morphological features of these two highly comparable species, often considered as morphotypes of the same species. Thanks to the revision of a large sample of N. sinensis from Chinese localities of the Yushe Basin (Shanxi Province), new scores for this species have been calculated. The results presented here confirms a strong adaptation to an omnivorous diet, as emerged from morphofunctional evidence in recent literature.